Leucas sahyadriensis (Lamiaceae: Lamioideae) an overlooked new endemic species from India and notes on Leucas chinensis - Sunojkumar, Purayidathkandy (Phytotaxa, 2019)
Wight’s specimen from Peninsular India which Bentham considered as Leucas chinensis is different from Retzius specimen from China. A lectotype for this name is selected from specimens collected by Bladh for Retzius in China. In contrast, Wight’s specimen represents a new species endemic to southern Western Ghats, having long branches, broadly ovate leaves, funnel shaped calyx with a wide mouth and stellately spreading, broadly triangular teeth and the corolla 16–17 mm long. The new species is named Leucas sahyadriensis. Detailed description, illustration, photographs, distribution maps and a table showing its differences from allied species are provided.